PENGARUH PEMBELAJARAN BERBASIS MASALAH OPEN-ENDED TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH OLEH SISWA - Suwandi, Tri; Hasnunidah, Neni; Marpaung, Rini Rita T. (FKIP Universitas Lampung, 2016)
: The Effects of Problem Based Learning Open-Ended Type towards The Improving of Students’ Problem Solving Skills. This study aimed to determine the effect of using openended PBM models in improving problem-solving skills of students. This study was a quasiexperimental with pretest posttest designs not equivalent. Samples were students in class X1 and X6 selected from the population by using cluster random sampling. This research data were in the form of quantitative and qualitative data. The quantitative data were obtained from the average value of pretest and posttest that were statistically analyzed using t-test at 5% confidence level through SPSS 17. Qualitative data were in the form of a description of the problem solving ability of students, student learning activity data, and the questionnaire responses of students to use open-ended PBM model which were analyzed descriptively. The average percentage of students’ activity in all aspects observed in the experimental class is higher than the control class (experimental = 81.32; control = 64.22). Therefore, learning by using PBM model of open-ended can influence the increasing of problem solving skills by students. Keywords: problem-based learning model open-ended type, problem-solving skills, biology learning, biodiversity. DOI: http://dx.doi.org/10.23960/jpp.v6.i2.201601